2010
DOI: 10.1161/atvbaha.110.203943
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulin-Like Growth Factor-1 and Its Binding Protein-3

Abstract: Objective-The metabolic and genetic correlates of circulating insulin-like growth factor-1 (IGF-1) and its main circulating carrier, IGF-1-binding-protein-3 (IGFBP-3), are unclear. Methods and Results-We measured serum IGF-1 and IGFBP-3 concentrations in a sample of the Framingham Heart Study (Nϭ3977, aged 40Ϯ9 years, 46% male) and evaluated their relations to cardiovascular risk factors using multivariable regression. Serum IGF-1 was inversely correlated with age, body mass index, total cholesterol, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
65
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 48 publications
20
65
0
Order By: Relevance
“…Specifically, a number of regulators of metabolic and adipocyte homeostasis appeared to predict adverse events in our study: IGF1 is involved in adipocyte proliferation and differentiation, and whereas some studies support a protective role with respect to atherosclerosis, others have not shown any association with coronary artery disease 17, 18. In the FHS, lower IGF1 levels were previously reported to be associated with adverse metabolic risk,19 and we now show an association with mortality in both single‐ and multimarker models. IGF1, in turn, is regulated by insulin‐like growth factor binding protein 1 (IGFBP1), which plays a role in glucose counter‐regulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, a number of regulators of metabolic and adipocyte homeostasis appeared to predict adverse events in our study: IGF1 is involved in adipocyte proliferation and differentiation, and whereas some studies support a protective role with respect to atherosclerosis, others have not shown any association with coronary artery disease 17, 18. In the FHS, lower IGF1 levels were previously reported to be associated with adverse metabolic risk,19 and we now show an association with mortality in both single‐ and multimarker models. IGF1, in turn, is regulated by insulin‐like growth factor binding protein 1 (IGFBP1), which plays a role in glucose counter‐regulation.…”
Section: Discussionsupporting
confidence: 78%
“…Last, resistin is an adipokine that impairs insulin action and is thought to represent a mechanistic link of obesity with diabetes mellitus 17, 18, 26. In previous FHS analyses, resistin was reported to be associated with incident HF, and it also predicted adverse outcomes among patients with stable coronary disease in the Heart and Soul study 19, 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…In two previous studies on the association of IGF1 with the metabolic syndrome in older populations, U-shaped relationships have been reported (9,10). Others report low IGF1 values to be related to a greater metabolic burden (11,12,13,14). These cohort studies only speculate about the role of this association in the development of CVD over time.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast to these findings, population-based studies (11,12,15,18) mainly revealed conflicting results regarding the associations of IGF1 or IGFBP3 levels with lipid levels. Filipsson Nyström et al (18) detected an inverse relation between IGF1 and cholesterol levels in 202 men and women.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies, IGF1 levels were linked to cardiovascular risk factors such as insulin resistance (7), metabolic syndrome (8,9), and also single lipid levels (10,11,12,13,14,15,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%